EVALUATION OF ANTIMICROBIAL ACTIVITY OF GREEN-SYNTHESIZED MANGANESE OXIDE NANOPARTICLES AND COMPARATIVE STUDIES WITH CURCUMINANILINE FUNCTIONALIZED NANOFORM - M, Muhamed Haneefa; M, Jayandran; V, Balasubramanian (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Metal oxide nanoparticles are widely attracted researchers due to their potential applications in a variety of fields, especially medicinal importance. It has been shown that biofunctionalization of metal nanoparticles with the specified bioactive materials produces the significantly improved bioactive materials with the essential biological properties and advanced features. According to the reports, manganese oxide nanoparticles (MONPs) possess highly magnetic properties leads to develop for use in research and biomedical applications. In this evaluation, we focused on the synthesis of MONPs through a green methodology and their antimicrobial activity changes when functionalized with curcuminaniline derived from turmeric plants. Methods: First, curcumin has been isolated from turmeric plant (BSR-01) to synthesize curcuminaniline biomaterial. On the other hand, manganese nanoparticles are synthesized by the green synthesis method using lemon extract and curcumin. Finally, the synthesized curcuminaniline is functionalized with MONPs. The synthesized nanoparticles are characterized by ultraviolet-visible, Fourier transform infrared, scanning electron microscope and transmission electron microscopy techniques. The antimicrobial activity of the obtained nonfunctionalized and biofunctionalized nanoforms are tested against some Gram-negative and Gram-positive bacterial strains as well as fungal strains. Results: The morphological studies represented that MONPs are of eclipsed and spherical morphology with size about 50Â±5 nm and biofunctionalized nanoparticles are of spherical morphology with size about 50Â±10 nm. The antibacterial and antifungal tests revealed that biofunctionalized MONPs are exhibited significantly higher antimicrobial activity. Conclusion: This investigation clearly demonstrated that MONPs are shown significantly higher biocidal activity when biofunctionalized with modified curcumin material. This may help in the future medicinal and pharmaceutical industries to develop new inventions. Keywords: Green synthesis, Nanoparticles, Curcumin, Curcuminaniline, Soxhlet extraction, Antimicrobial activity.